The Influence of Pipe Bending Curvature on H2-O2 Gaseous Detonation Wave Front - Hui Zhao; Huiyuan Li; Haitao Zhao; Leisheng Li; Jian Li (Applied Sciences, 2021)
The influence of different bend curvatures on the detonation wave propagation was analyzed by an advanced numerical simulation system. The mechanism of propagation properties is revealed by cellular structure, internal and external boundary pressure distribution, propagation process of detonation wave and chemical reaction. The cellular structure and detonation wave front of bend with different curvature are very different. The simulation results show that the detonation wave with regular cell structure propagating through the curved parts induces detonation cell size increased by diffraction near the inner wall while detonation reflected on the bottom surface resulting in decrease of cell size. Detonation wave was affected by the rarefaction wave and compression wave in the bent pipe. The pressure distribution of the bend shows that the peak pressure in the 450 curvature is the largest, which should be paid more attention in industrial design. The chemical reaction could indicate the propagation characteristics of detonation wave, and different propagation characteristics have different profiles of chemical components.